Biosynthesis of phosphoinositol-containing sphingolipids from phosphatidylinositol by a membrane preparation from Saccharomyces cerevisiae. - Becker, G W (1980)
Incubation of membranes prepared from Saccharomyces cerevisiae with [32P]phosphatidyl[3H]inositol resulted in the transfer of both labels to two products which were characterized as two species of inositolphosphoceramide, differing in the ceramide portion of the molecule. The products were characterized on the basis of stability in mild alkali, mobility on silica gel-impregnated paper, chromatography on silicic acid columns, and release of inositol phosphate upon base hydrolysis. The reaction did not require the addition of metals, nor was it inhibited by ethylenediaminetetraacetic acid. The detergents Triton X-100 and Tween 20 provided little, if any, stimulation. At relatively high concentrations of phosphatidylinositol (1 to 4 mM), the in vitro rate was about 20% of the in vivo rate. Although ceramide was a logical substrate, the reaction could not be greatly stimulated by the addition of ceramides containing mono- and dihydroxy fatty acids. In addition, incubation of yeast membranes with [32P]phosphatidylinositol gave rise to a product that was chromatographically indistinguishable from the major yeast phosphosphingolipid, mannose-(inositol-P)2 ceramide.